Multicolor time‐resolved Förster resonance energy transfer microscopy reveals the impact of GPCR oligomerization on internalization processes. Issue 6 (17th February 2015) - Faklaris, Orestis; Cottet, Martin; Falco, Amandine; Villier, Brice; Laget, Michel; Zwier, Jurriaan M.; Trinquet, Eric; Mouillac, Bernard; Pin, Jean‐Philippe; Durroux, Thierry
ABSTRACT: Identifying the interacting partners and the dynamics of the molecular networks constitutes the key point in understanding cellular processes. Different methods often based on energy transfer strategies have been developed to examine the molecular dynamics of protein complexes. However, these methods suffer a couple of drawbacks: a single complex can be studied at a time, and its localization and tracking cannot generally be investigated. Here, we report a multicolor time‐resolved Förster resonance energy transfer microscopy method that allows the identification of up to 3 different complexes simultaneously, their localization in cells, and their tracking after activation. Using this technique, we studied GPCR oligomerization and internalization in human embryonic kidney 293 cells. We definitively show that receptors can internalize as oligomers and that receptor coexpression deeply impacts oligomer internalization processes.— Faklaris, O., Cottet, M., Falco, A., Villier, B., Laget, M., Zwier, J. M., Trinquet, E., Mouillac, B., Pin, J.‐P., Durroux, T. Multicolor time‐resolved Förster resonance energy transfer microscopy reveals the impact of GPCR oligomerization on internalization processes. FASEB J. 29, 2235‐2246 (2015). www.fasebj.org